2009
DOI: 10.1016/j.cell.2009.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Structure of N-Terminal Domain of NPC1 Reveals Distinct Subdomains for Binding and Transfer of Cholesterol

Abstract: SUMMARY LDL delivers cholesterol to lysosomes by receptor-mediated endocytosis. Exit of cholesterol from lysosomes requires two proteins, membrane-bound Niemann-Pick C1 (NPC1) and soluble NPC2. NPC2 binds cholesterol with its isooctyl side chain buried and its 3ß-hydroxyl exposed. Here, we describe high-resolution structures of the N-terminal domain (NTD) of NPC1 and complexes with cholesterol and 25-hydroxycholesterol. NPC1(NTD) binds cholesterol in an orientation opposite to NPC2: 3ß-hydroxyl buried and isoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
720
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 609 publications
(741 citation statements)
references
References 41 publications
19
720
0
2
Order By: Relevance
“…It has been demonstrated that a water soluble fragment of NPC1 binds cholesterol in an orientation opposite to NPC2 (Infante et al 2008). Based on these results, it has been postulated that, after liberation from LDL, cholesterol is bound by NPC2 which carries it to the lysosomal membrane, where it transfers to the N-terminal domain of the membrane bound NPC1 (Kwon et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a water soluble fragment of NPC1 binds cholesterol in an orientation opposite to NPC2 (Infante et al 2008). Based on these results, it has been postulated that, after liberation from LDL, cholesterol is bound by NPC2 which carries it to the lysosomal membrane, where it transfers to the N-terminal domain of the membrane bound NPC1 (Kwon et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Infante et al discovered that NPC1's N-terminal domain binds cholesterol and this capacity is required for lysosomal cholesterol export (10,11). The N-terminal domain binds cholesterol in opposite orientation from NPC2, suggesting the possibility of a direct hand-off of cholesterol from a soluble NPC2 protein to membrane-associated NPC1 (12). Although this model is very attractive, a direct interaction between the NPC1 N-terminal domain and NPC2 protein has not been detected to date.…”
mentioning
confidence: 92%
“…The capped form may represent an inactive state of NPC1 protein because surface residues needed for interaction with NPC2 (and Ebola virus) are shielded by the presence of the N-terminal domain. Nevertheless, both the N-terminal domain and lumenal domain 2 are likely to interface with NPC2 as part of the cholesterol transfer process (12,13,20). Both the cryo-EM and crystal structures highlight the unusual height of the protein in relation to the lysosome's internal limiting membrane (5,20).…”
mentioning
confidence: 99%
See 2 more Smart Citations